Labial Adhesion with Acute Urinary Retention Secondary to Vaginitis - Şenol Şentürk; Pelin Üstüner; Gülşah Balık; Mehmet Kağıtcı; Ülkü Mete Ural; Figen Kır Şahin (Hindawi Limited, 2014)
Labial adhesion occurs most often in infants and girls and is usually associated with low estrogen levels. Labial adhesion in the reproductive age group is extremely rare due to abundance of estrogen. Herein we present a case of almost complete labial adhesion with acute urinary retention in a 21-year-old virgin woman secondary to a probable untreated severe vaginitis.